Direct Blow-Spinning of Nanofibers on a Window Screen for Highly Efficient PM2.5 Removal - Khalid, Bilal; Bai, Xiaopeng; Wei, Hehe; Huang, Ya; Wu, Hui; Cui, Yi (Nano letters, 2017)
Particulate matter (PM) pollution has caused many serious public health issues. Whereas indoor air protection usually relies on expensive and energy-consuming filtering devices, direct PM filtration by window screens has attracted increasing attention. Recently, electrospun polymer nanofiber networks have been developed as transparent filters for highly efficient PM2.5 removal; however, it remains challenging to uniformly coat the nanofibers on window screens on a large scale and with low cost. Here, we report a blow-spinning technique that is fast, efficient, and free of high voltages for the large-scale direct coating of nanofibers onto window screens for indoor PM pollution protection. We have achieved a transparent air filter of 80% optical transparency with >99% standard removal efficiency level for PM2.5. A test on a real window (1 m × 2 m) in Beijing has proven that the nanofiber transparent air filter acquires excellent PM2.5 removal efficiency of 90.6% over 12 h under extremely hazy air conditions (PM2.5 mass concentration > 708 μg/m3). Moreover, we show that the nanofibers can be readily coated on the window screen for pollution protection and can be easily removed by wiping the screen after hazardous days.